Changing incidence of reported viral hepatitis in China from 2004 to 2016: an observational study - Yanhang Gao; Ruihong Wu; Mingyuan Zhang; Hongqin Xu; Julia Uhanova; Robert Gish; Xiaoyu Wen; Qinglong Jin; Minuk Y Gerald; M H Nguyen; J Niu (BMJ Open)
Objective China’s national hepatitis burden is high. This study aims to provide a detailed national-level description of the reported incidence of viral hepatitis in China during 2004–2016.Design Observational study.Setting Data were obtained from China’s National Notifiable Disease Reporting System, and changing trends were estimated by joinpoint regression analysis.Participants In this system, 16 927 233 reported viral hepatitis cases occurring during 2004–2016 were identified.Primary outcome measure Incidence rates per 100 000 person-years and changing trends were calculated.Results There were 16 927 233 new cases of viral hepatitis reported in China from 2004 to 2016. Hepatitis B (HBV) (n=13 543 137, 80.00%) and hepatitis C (HCV) (n=1 844 882, 10.90%) accounted for >90% of the cases. The overall annual percent change (APC) in reported cases of viral hepatitis and HBV were 0.3%(95% CI −2.0 to 0.8, p=0.6) and −0.2% (95% CI −1.6 to 1.2, p=0.8), respectively, showing a stable trend. HBV rates were highest in the 20–29 year old age group and lowest in younger individuals, likely resulting from the universal HBV vaccination. The reported incidence of HCV and hepatitis E (HEV) showed increasing trends; the APCs were 14.5% (95% CI 13.1 to 15.9, p<0.05) and 4.7% (95% CI 2.8 to 6.7, p<0.05), respectively. The hepatitis A (HAV) reporting incidence decreased, and the APC was −13.1% (95% CI −15.1 to −11.0, p<0.05). There were marked differences in the reporting of hepatitis among provinces.Conclusions HBV continues to constitute the majority of viral hepatitis cases in China. Over the entire study period, the HBV reporting incidence was stable, the HCV and HEV incidence increased and the HAV incidence decreased. There were significant interprovincial disparities in the burden of viral hepatitis, with higher rates in economically less-developed areas. Vaccination is important for viral hepatitis prevention and control.